Research on Anti-inflammatory Targets and Mechanisms of alkaloids in Picrasma quassioides Benn Through Network Pharmacology - Qijia Xu; Kai Wang; Yaoyao Xu; Yinhe Gao; Ge Wang; Sheng Liu; Feng Zhao (Universidade de São Paulo, 2023)
Abstract This study aimed to investigate the molecular mechanism of Picrasma quassioides Benn against inflammation by means of network pharmacology. The paper will provide a reference for multi-target and multi-channel treatment of inflammation with traditional Chinese medicine. Through screening and analysis, 11 active ingredients and 109 anti-inflammation prediction targets were obtained and constructed a compound-target network. The targets such as VEGFA, TLR4 and STAT3 may play a crucial role. Network enrichment analysis showed that the 109 potential targets constitute a number of pathways or inflammatory reactions closely related to inflammation, including NF-κB signaling pathway and MAPK signaling pathway. The docking results indicated that the binding energy of Picrasidine Y and the inflammatory factors VEGFA is the highest. This study predicted the role of multiple active compounds in the alkaloids of Picrasma in the inflammatory response, and provided a theoretical basis for the anti-inflammatory mechanism of Picrasma.